Morphometric study of vocal fold of different sexes of Bangladeshi cadaver - Ara, A; Khalil, M; Sultana, SZ; Ahmed, MS; Akhter, F; Haque, N; Haque, MA; Choudhury, AI (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):173-5. The abstract of this article is available on the PubMed website